Pengaruh Foreign Direct Investment (FDI) dan Daya Saing Terhadap Ekspor (Studi Pada Sektor Industri Manufaktur Indonesia Tahun 2004-2013) - Aulia Hadin Salsabila (Jurnal Administrasi Bisnis, 2015)
Globalization in the economic field has encourage economic participation between countries. Every economy in the world has the goal to master and compete in the global market. Export is one of the economic activities undertaken to market their products outside national borders. By doing so, export requires a driving factor, the driving factors used in this study are FDI (Foreign Direct Investment) and competitiveness.The aim of this study is to determine the influence of FDI and competitiveness against exports on Indonesia’s manufacturing industries. This study using an equations model analysis with Ordinary Least Square (OLS) from the first quarter of 2004 – the fourth quarter of 2013. According to the result of simultaneous test indicating that FDI and competitiveness has significant effect on export .Furthermore, the partial test results indicates that each variable of FDI and competitiveness showed a significant effect on export. Keywords : FDI, Competitiveness, RCA, and Exports.